Association between occupational stress and risk of overactive bladder and other lower urinary tract symptoms: A cross‐sectional study of female nurses in China123. Issue 3 (17th August 2012) - Zhang, Chunfang; Hai, Ting; Yu, Luping; Liu, Shijun; Li, Qing; Zhang, Xiaowei; Xu, Tao; Wang, Xiaofeng
Abstract Aims To evaluate the prevalence of overactive bladder (OAB) and other lower urinary tract symptoms (LUTS), and their association with occupational stress in female nurses in China. Methods From September 2010 to March 2011, 1, 135 registered female nurses with one or more years of nursing experience, were cluster‐sampled. The participants completed questionnaires on LUTS‐related symptoms and Occupational Stress Inventory‐Revised (OSI‐R) tests. Multiple logistic regressions were performed to evaluate the independent impact of perceived occupational stress on OAB and other LUTS, adjusting for age, body mass index (BMI), and history of childbearing and pelvic surgery. Results 1, 070 valid responses to questionnaires were obtained. The prevalence of OAB was 27.57% (95% CI: 24.89–30.25%). LUTS of any types occured in 89.63% of nurses, with 64.39% reporting urgency, 27.10% reporting increased daytime frequency, 17.88% reporting nocturia and 21.03% reporting urge incontinence. The occupational stress and psychological strain levels of nurses were higher than those of normative populations, while their coping resources were lower. Most of the sub‐scales of occupational stress and psychological strain showed higher results for nurses with OAB than for those OAB‐free, while coping resources were not found to make any statistically significant differences. After adjusting age, BMI, and childbearing and pelvic surgery history, each sub‐scale of OSI‐R was found to be associated with at least one type of LUTS. Conclusions The prevalence of OAB and other LUTS is high among female nurses in China, and occupational stress may be a contributing factor. Neurourol. Urodynam. 32: 254–260, 2013. © 2012 Wiley Periodicals, Inc.